2016
DOI: 10.1534/genetics.115.184127
|View full text |Cite
|
Sign up to set email alerts
|

A General Approximation for the Dynamics of Quantitative Traits

Abstract: Selection, mutation, and random drift affect the dynamics of allele frequencies and consequently of quantitative traits. While the macroscopic dynamics of quantitative traits can be measured, the underlying allele frequencies are typically unobserved. Can we understand how the macroscopic observables evolve without following these microscopic processes? This problem has been studied previously by analogy with statistical mechanics: the allele frequency distribution at each time point is approximated by the sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 48 publications
(55 reference statements)
0
36
0
Order By: Relevance
“…The derived population may thereby undergo a population size reduction (bottleneck). It is therefore important to study polygenic selection for populations that are finite in size (Bod'ová et al, 2016;Franssen et al, 2017) and may undergo size changes in time.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…The derived population may thereby undergo a population size reduction (bottleneck). It is therefore important to study polygenic selection for populations that are finite in size (Bod'ová et al, 2016;Franssen et al, 2017) and may undergo size changes in time.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…The surprisingly good approximation properties of the DynMaxEnt method, as documented by the numerical results in [6] and Section 6 of this paper, suggest that the infinitely-dimensional dynamics of the Fokker-Planck equation (1.1) can be well approximated by suitable finitely-dimensional dynamical systems. This is reminiscent of the recent series of works of E. Titi and collaborators [18,12,2,17,1] where a data assimilation (downscaling) approach to fluid flow problems is developed, inspired by ideas applied for designing finite-parameters feedback control for dissipative systems.…”
mentioning
confidence: 59%
“…It has been applied, e.g., to modeling of cosmic ray transport [14], general Fokker-Planck equation [21], analysis of genetic algorithms [22], and population genetics [23,4,6]. In [6] it is observed that the "classical" DynMaxEnt method cannot be applied in the regime of small mutations, and the theory is extended for this regime to account for changes in mutation strength. Surprisingly, systematic numerical simulations document superb approximation properties of the method even far from the quasi-stationary regime.…”
Section: The Dynamical Maximum Entropy Approximationmentioning
confidence: 99%
See 2 more Smart Citations